Evaluasi Progran Maghrib Mengaji Kementerian Agama di Sumatera Utara - Syaukani Syaukani (Intiqad: Jurnal Agama dan Pendidikan Islam, 2022)
The purpose of this research is to evaluate the program insiated by the Ministry of Religious Affairs, reciting the holy Quran after maghrib. This study uses CIPP model of evaluation. The samples are taken from several mosques and homes that organized maghrib mengaji (reciting Quran) program in Medan city. The study concludes that the program can be continued because it has revitalized the Muslims culture in reciting Quran after maghrib prayer. This program has achieved the main goal of the governments program that is to restore the Indonesian muslim tradition and the output of the program is absolutely positive since many people have participated in the program.